Ce[N(SiMe3)2]3(THF)3-catal yzed hydroboration of CO2, esters and epoxides with pinacolborane: selective synthesis of methanol in multigram scale - Hossain, Md Jabed; Shah, Brij Kumar; Dash, Soumya Ranjan; Vanka, Kumar; Khan, Shabana (Chemistry-A European Journal, 2025)
In this work, we have reduced CO2 with HBpin to afford borylated methanol product selectively in similar to 99 % yield using Ce[N(SiMe3)(2)](3)(THF)(3) as a catalyst. This led to multigram scale isolation of methanol obtained from CO2 reduction via the hydrolysis of borylated methanol, this establishes the potential of Ce[N(SiMe3)(2)](3)(THF)(3) as an efficient homogeneous catalyst for the bulk scale methanol synthesis. A practical application of this catalytic system was also shown by reducing CO2-containing motorbike exhaust efficiently and selectively. Further, C-O bond activation of esters and epoxides using HBpin and 1-2 mol % of Ce[N(SiMe3)(2)](3)(THF)(3) at 60 degrees C afforded the borylated alcohols in good to excellent yields, which can easily be hydrolysed to the eco-friendly corresponding alcohol. The stoichiometric experiments were performed to prove the formation of in-situ generated cerium hydride [Ce]-H as an active catalyst.
Keywords: Cerium; CO2 reduction; Epoxide; Ester; Hydroboration; Lanthanides